Wykorzystanie kart kontrolnych do stabilizacji procesów gospodarczych - Kuźmiński, Łukasz; Peternek, Piotr (The application of control charts for stabilization of economic process, 2005)
In the article capabilities of employment of control charts for description of quality and stability of economic process of enterprise are considered. In the first part of the paper there are some chosen control charts are described. All control charts are illustrated with simple examples. The second part concerns regressive approach. It presents regressive control charts in application for description of stability cost level of enterprise. There control charts with a drift as well as linear and unlinear regression charts are considered.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (15); 2005; nr 1096, s. 361-375